Development of fire protection duct for the safety-relevant circuits - Lim, You Yi (2023)
Fire protection ducts store and protect electrical cables during a fire outbreak. The cables provide power supplies to the active fire protective system (e.g., water sprinklers, fire alarms) and extend the time for evacuation. Fire protection duct can be fabricated by combining and assembling fire-retardant boards. The project scope focuses on formulating the water-based intumescent binder (WIB) as the fundamental of the fire-retardant board. W-IB was proven to have better properties than the commercial magnesium oxide (MgO) board, especially in fire resistivity. The commercial MgO board possesses a low resistivity to fire and water and is not able to provide long-term protection of the underlying substrate from a high temperature and moisture environment. In the analysis, four groups of W-IB were formulated and analysed through fire resistance testing (e.g., Bunsen burner test), chemical testing (e.g., static immersion test), mechanical testing (e.g., adhesion strength test), thermal testing (e.g., TGA test), and physical testing (e.g., SEM/EDX test, FTIR test). Next, WIB and vermiculite were combined to make fire-retardant board prototypes. To ascertain the compositions' best performance, a half-hour small-scale fire, a density measurement, a sound insulation, and a three-point flexural tests were conducted. The leading-performing fire-retardant board was then cast using the best-performing compositions. The capabilities of the fire-retardant board and the commercial MgO board were compared using a 1-hour small-scale fire test and density measurement test. The leading-performing fire-retardant board was then used to construct a small-scale fire protection duct. The results of all the tests revealed that, both pre and post of the 1-hour small-scale fire test, fireretardant board prototype 4 (P4) has a lower weight loss percentage than commercial MgO board. Prototype P4 has a weight loss of 20.6 % lower than commercial MgO board. Thus, prototype P4 has better suitability to construct fire protection duct. On the other hand, prototype P4 also showed a lower temperature profile (100 ℃) than the commercial MgO board (220 ℃) when conducting the 1-hour small-scale fire test. Therefore, prototype P4 possesses an effective W-IB that can resist the fire propagation and remain its technical integrity after a 1-hour small-scale fire test.